PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENGURANGAN BILANGAN CACAH DI KELAS I GUGUS I KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Khairunnisa, Gina; Yarisda Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the influence of the Problem Based Learning model on students' learning outcomes in number subtraction lessons in Grade I of Cluster I, Lengayang District Pesisir Selatan Regency. The type of this research is quasi-experimental design with a nonequivalent control group design. The population of this study is all first-grade students in Group I, Lengayang District. Sampling was conducted using purposive sampling techniques, resulting in class I.A UPT SDN 28 Pasar Gompong as the experimental class and class I.B UPT SDN 28 Pasar Gompong as the control class. The instrument used in this study was an objective test in the form of multiple-choice questions. Based on the research results, the average posttest score in the experimental class was higher, at 88.10, compared to the control class at 77.62. After conducting the hypothesis test, tcount = 2.1577 was obtained, while ttabel at a 95% confidence level ( = 0.05) is 2.02. Thus, H0 is rejected and H1 is accepted, because tcount > ttabel, so it can be concluded that there is a significant influence of the Problem Based Learning model on students' learning outcomes in number subtraction lessons in class I Group I, Lengayang District Pesisir Selatan Regency.